The Effect of Papaya and Guava Leaf Decoction on the Adequacy of Breast Milk in Postpartum Mothers - Choirunissa, Risza; Indrayani, Triana (Indonesian Journal of Global Health Research, 2024)
Breast milk is a source of food that contains complete nutrition for babies, increases endurance, increases intelligence will establish affection between mother and child. Data on postpartum mothers in 2023 is the incidence of adequacy of 50 cases. Of the 38 respondents, about 76% of mothers said breast milk was not smooth and milk did not come out after giving birth and milk only came out two days after giving birth but the amount was small and the amount of breast milk was small, so mothers gave formula milk. The purpose of this study is to evaluate the effect of papaya and guava leaf decoction on the adequacy of breast milk production in postpartum mothers in Bekasi City. to determine the effect of papaya leaves and guava seeds with the adequacy of breast milk on postpartum mothers in East Bekasi. The design used in this study is Quasi Experimental with a one group pretest – posttest design approach. The sample in this study amounted to 30 respondents consisting of 15 intervention respondents and 15 control respondents with purposive sampling techniques. In this study on the effect of papaya and guava leaf decoction on breast milk adequacy in postpartum mothers in Bekasi City, data were collected using observation sheets for 30 respondents divided into intervention and control groups, analyzed with an Independent T-Test, showing significant improvement in the intervention group's breast milk production from a pretest average of 41.13 to a posttest average of 92.22, compared to the control group's increase from 44.45 to 66.67, concluding papaya leaf's positive influence on milk adequacy.The data were analyzed using a t-independent test. The instrument used is an observation sheet. The results of univariate analysis in the intervention group obtained an average pretest score of 41.13 and posttest of 92.22, while in the control group obtained an average pretest value of 44.45 and posttest of 66.67. The results of the Independent T-Test test with a P-Value significance value of 0.003 which means there is an influence of papaya leaves on the adequacy of breast milk in nursing mothers. The conclusion of the research results is the influence of papaya leaves on the adequacy of breast milk in nursing mothers. Breastfeeding mothers are expected to pay attention to what is consumed to support the smooth running of breast milk so that the baby is met with the needs of mothers who have sufficient milk.